Vinte anos da política do ciclo básico na rede estadual paulista - Duran, Marília Claret Geraes; Alves, Maria Leila; Palma Filho, João Cardoso [UNESP] (Fundação Carlos Chagas, 2005)
From a historical-critical perspective, this article deals with the trajectory of the basic cycle in São Paulo State school system from the moment of its creation till the 1990s. It also discusses the actions and reactions brought about by the proposal and by the curricular reorganization of the middle school resulting from this initiative. The documental study starts from the motivations that guided the education policy at a moment of political opening, when the first elected government took office in the State of São Paulo, after the long period of military regime. The varied reactions from education professionals and from civil society, most of which were against the measures set forth, are then analyzed. What are the reasons that have systematically led to the failure of proposals committed to ensure regular education for people on the lowest incomes? The discussion highlights the strong presence of a conservative thought that permeates pedagogical culture in Brazil, that is against proposals that, similar to the one of basic cycle, are committed to the democratization of education.

Este artigo aborda, numa perspectiva histórico-crítica, o percurso do ciclo básico na rede estadual paulista, desde sua criação até os anos iniciais da década de 90, discutindo ainda as ações e reações desencadeadas pela proposta e pela reorganização curricular do ensino fundamental decorrentes dessa iniciativa. A pesquisa documental realizada parte das motivações que direcionaram a política educacional no momento de abertura política, em que assumia o poder o primeiro governo eleito no Estado de São Paulo após longo período de regime militar, e passa pela análise dos diferentes tipos de reações da rede de ensino e da sociedade civil, a maior parte delas contrárias às medidas encaminhadas. Quais as razões que têm levado sistematicamente à desmobilização de propostas comprometidas com a garantia da escolaridade regular das camadas mais pobres da população? A análise realizada evidencia a forte presença do pensamento conservador impregnado na cultura pedagógica brasileira, que se manifesta diante de propostas, como a do ciclo básico, comprometidas com a democratização do ensino.
Twenty years of basic cycle policy in São Paulo State school system
Keywords: EDUCATIONAL POLICIES; PUBLICS POLICIES; BASIC EDUCATION; PUBLIC EDUCATION; POLÍTICAS EDUCACIONAIS; POLÍTICAS PÚBLICAS; CICLO BÁSICO; ENSINO PÚBLICO